Les réactualisations discursives de la dénomination de «réfugié» - Paľová, Mária; Zeleňáková, Mariana (Neophilologica, 2017)
The semantic description of the concept of “refugee” oscillates today between the stability of some categorization features taken from the definition of refugee under the Geneva Convention and plasticity in the discursive construction of meaning due to strong media influence. The meaning of individual phrases is analysed on a representative corpus of Slovak media discourse of 2015 from the perspective of motifs-profiles-themes.